On streamlining the Ukrainian names of plants. Information 5. Species names for pome fruit crops - В. М. Меженський (Plant Varieties Studying and Protection)
To analyse the modern classification and nomenclature of species of pome fruit crops which varieties are listed in the State Register of Plants Varieties Suitable for Dissemination in Ukraine, and improve terminological system of the Ukrainian names of both species and garden crops. Results. Fruit cultivars and most apple clonal rootstocks belong to Malus pumila, and ornamental cultivars belong to Malus gloriosa. The most common scientific name of the cultivated apple, especially among horticulturists, is Malus domestica, although according to the principle of priority the name Malus pumila should have the advantage. As far as Nomenclature Committee for Vascular Plants has rejected the proposal to conserve the name Malus domestica, Malus pumila is correct name for the cultivated apple. The use of synonymic name Malus domestica should be avoided in both scientific and scientific-popular papers for stability of nomenclature. Pear cultivars listed in the State Register of Plants Varieties Suitable for Dissemination in Ukraine are presented by Pyrus communis, and pear rootstocks – by Cydonia oblonga. Fruit cultivars of the latter belong to separate fruit crop named quince. An apple-quince hybrid was registered as universal clonal rootstock for pome fruit crops. The State Register of Plants Varieties Suitable for Dissemination in Ukraine also contains nonconventional fruit crops such as Chaenomeles and hawthorn that consist of some species and nothospecies. Conclusions. In scientific publications one should stop the use of synonymic name Malus domestica in favour of the correct name for cultivated apple Malus pumila. Apple, pears and Chaenomeles cultivars listed in the State Register of Plants Varieties Suitable for Dissemination in Ukraine have a complex multispecies origin whereas quince, hawthorn and pear roostock cultivars systematically are monospecies. A universal roootstock of pome fruit crops is Cydolus, or apple-quince, that resulted from interspecies hybridization between quince and apple. Refusal Refuse to use obsolete names of fruit plants species will promote harmonization of professional language.